Short-term cardiovascular and mental health responses to Shinrin-Yoku (forest bathing): a systematic review and meta-analysis - Andrade, Aurélio Matos; Durães, Suzane da Fonseca; Franco Netto, Lorena Covem Rosa; Fenner, André Luiz Dutra; Carvalho, Marco Aurélio Bilibio; Franco Netto, Guilherme (Frontiers in Psychology, 2026)
Interest in the health benefits of Shinrin-Yoku (forest bathing) has increased in recent years, although evidence regarding its efficacy in preventing and managing circulatory problems and mental disorders remains limited. This study conducted a systematic review with meta-analysis to evaluate the effects of forest bathing on these conditions. Following PRISMA guidelines and registration on the Open Science Framework (OSF), a systematic literature search was performed in major databases including PubMed, Embase, Web of Science, Scopus, Lilacs, IBECS, WPRIM, PsyINFO, and ProQuest in October 2024. Review Manager software was used to calculate mean differences (MD) between pre- and post-intervention outcomes, and the certainty of evidence was assessed using the GRADE. A total of 718 records were identified, of which 11 studies met the inclusion criteria. Forest bathing was associated with a reduction in heart rate (MD = −4.00; 95% CI = −6.90 to −1.09), tension-anxiety (MD = −0.79; 95% CI = −1.13 to −0.46), and depression despondency (MD = −0.68; 95% CI = −1.03 to −0.34), with confidence intervals that did not cross the effect line. However, heterogeneity among studies ranged from moderate to very high (I2 = 49%–87%), particularly for psychological outcomes. Although general effect tests demonstrated strong statistical significance for several psychological outcomes (p < 0.00001), the certainty of the evidence was classified as very low according to the GRADE, mainly due to the risk of bias, inconsistency, and imprecision. Forest bathing should be interpreted as a potential complementary practice for health promotion, and not as an individual preventive or therapeutic intervention for cardiovascular or mental disorders.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/XETNK.